Evaluation of the impact of the EU structural support on the competitiveness of Lithuanian economics - Gasparėnienė, Ligita; Remeikienė, Rita (Business, Management and Economics Engineering, 2016)
Increasing amounts of the EU structural support in Lithuania require theoretical and practical research to disclose the determinants that have a significant impact on the competitiveness of Lithuanian economics. The purpose of this article is to evaluate the impact of the EU structural support on the competitiveness of Lithuanian economics. The methods of the research include systematic and comparative analysis of the scientific literature, expert evaluation and linear regression. The research disclosed the main determinants of country’s competitiveness. The results have revealed that EU structural support has the most significant impact on Lithuanian engineering and technological infrastructure. The impact of the support on country’s macroeconomic, scientific and social environment can also be considered as significant. The EU structural support has medium strong impact on education and business environment conditions in Lithuania. It has been established that, in the field of business advancement, Lithuanian should be rated as medium competitive. Hence, the increase in country’s competitiveness by employing EU structural funds should be treated as one of priority aims. In addition, responsible authorities should perform with higher efficiency seeking for higher competitiveness of the country.